(untitled) (International Journal of Chemistry and Materials Research, 2023)
This study focused on developing a new copolymer binder from Polyvinyl acetate (PVAc) and Guna seed oil, in which the copolymer binder was used to formulate an emulsion paint. The emulsion paint formulated from the novel copolymer binder of polyvinyl acetate- hydroxylated guna seed oil (PVAc/HGSO) was characterised and compared with paint made from conventional polyvinyl acetate (PVAc) binder. Seed oil from guna was extracted mechanically using cold press method, and the extracted guna seed oil were successively subjected to epoxidation and hydroxylation reaction processes. The hydroxylated guna seed oil (HGSO) was copolymerised with conventional polyvinyl acetate in different ratio of 10 to 70% of hydroxylated oil, to formulate a novel PVAc/HGSO copolymer binder. The physico-chemical properties of the formulated copolymer binder were compared with the standard value acceptable in coating industry inorder to ascertain the better blend ratio that will be suitable for paint production. The better blend copolymer binder was used in production of an emulsion paint. The physico-chemical parameters on the formulated emulsion paint were compared with paint formulated using only PVAc as a binder and acceptable value in the coating industry. The novel formulated emulsion paint found to be increased in gloss, adhesion and flexibility, which are major setback in paint produced using conventional PVAc only as a binder. Therefore, the novel PVAc/HGSO can be used to produce an emulsion paint.